Satire and Political Subversion: Critical Discourse Analysis of Javanese Power Ethics in Serat Wicara Keras - Dewa Alfaquin Faturangga; Diefa Octavia Poetra; M. Syirojul Huda (Al-Absah: Journal of Civilization, Language, Literature, and History, 2026)
This study aims to analyze satire and political subversion in Serat Wicara Keras by R. Ng. Yasadipura II as a critique of Javanese power ethics. The research employs a qualitative method using Norman Fairclough’s Critical Discourse Analysis approach to examine the relationship between language, ideology, and power within the text. Data were collected through library research and textual analysis of verses containing socio-political criticism. The findings reveal that Yasadipura II utilizes satire, irony, pejorative metaphors, and moral symbolism as discursive strategies to criticize the moral decadence of the priyayi elite and the crisis of political legitimacy within the royal court. The criticism is conveyed indirectly through a hidden transcript mechanism, enabling symbolic resistance against feudal political culture without direct confrontation. This study also finds that the critical values contained in Serat Wicara Keras remain relevant to contemporary Indonesian politics, particularly regarding oligarchy, dynastic politics, corruption, and the crisis of leadership ethics. Therefore, Serat Wicara Keras is not only a literary and historical text but also a medium of socio-political criticism that reflects the relationship between language, culture, and power in the Javanese tradition.